Contested Racial Imaginings of the Serbian Self and the Romani Other in Serbia's Guča Trumpet Festival - Jelena Gligorijevic (MDPI, 2022)
In this article, I will address issues of race using the "Romani question" in Serbia's Guca trumpet festival as a case study. I will specifically consider a selection of Guca-related themes pertinent to the question of race, while simultaneously discussing the theoretical and ideological underpinnings of this complicated concept vis-a-vis issues of national identity representation in post-Milosevic Serbia. Informed by previous critical studies of race and popular music culture in South/Eastern Europe within the larger postcolonial paradigm of Balkanism, this work will seek to illustrate the ambiguous ways in which the racialization of the Serbian Self and the Romani Other is occurring in the Guca Festival alongside the country's and region's persistent denial of race. Using the above approaches, I will conduct a critical cultural analysis of selected racial issues in the festival with reference to eclectic sources, including more recent critical debates about race and racism in South/Eastern Europe within the broader context of postsocialist transition, EU integration, and globalization. My final argument will be that, despite strong evidence that a critical cultural analysis of the "Romani question" in Serbia's Guca Festival calls for a transnational perspective, earlier Balkanist discourse on Serbia's indeterminate position between West and East seems to remain analytically most helpful in pointing to the uncontested hegemony of Western/European white privilege and supremacy.